2021
DOI: 10.2196/23528
|View full text |Cite
|
Sign up to set email alerts
|

Building an Interactive Geospatial Visualization Application for National Health Care–Associated Infection Surveillance: Development Study

Abstract: Background The Centers for Disease Control and Prevention’s (CDC’s) National Healthcare Safety Network (NHSN) is the most widely used health care–associated infection (HAI) and antimicrobial use and resistance surveillance program in the United States. Over 37,000 health care facilities participate in the program and submit a large volume of surveillance data. These data are used by the facilities themselves, the CDC, and other agencies and organizations for a variety of purposes, including infecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Second, mosaic plots were designed to help analyze the association level between two or more categorical variables through the residual value and provide a way to visualize the relationships between the categorical variables [25]. The higher the standard residuals' value, the stronger the association between the categorical variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, mosaic plots were designed to help analyze the association level between two or more categorical variables through the residual value and provide a way to visualize the relationships between the categorical variables [25]. The higher the standard residuals' value, the stronger the association between the categorical variables.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, considerable resources might be wasted on dispatching EMS to respond to minor medical or trauma cases that do not require emergency or specialized pre-hospital medical care or transport to hospital. Research in England has suggested that profound and focused investigation strategies are needed to identify the dimensions of such decisions to formulate appropriate corrective strategies [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Visualization dashboards can inform decision-making and support behavior change in public health and health care services [ 22 - 25 ]. A recent review of the literature suggests that the strength of evidence on the effect of ICU visualization dashboards remains low [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visualization dashboards can inform decision-making and support behavior change in public health and health care services [22][23][24][25]. A recent review of the literature suggests that the strength of evidence on the effect of ICU visualization dashboards remains low [9].…”
Section: Comparison With Previous Workmentioning
confidence: 99%